Ordinary lives, extraordinary times? the terrible opportunity for sociological inquietude - Nico, M. (European Sociologist, 2020)
Ordinary lives, extraordinary times. Margaret Atwood explained in a TV interview the matrix in which she situates the stirring and thought-provoking dystopias she has shared with us. There are ordinary and extraordinary people, and there are ordinary and extraordinary times, she says. She writes about ordinary people in extraordinary times. The resemblance of this match between ordinary people (biographies) and extraordinary times (societies) with the current pandemic is overpowering. The pandemic is developing at unequal epidemiological speeds according to countries and their reactions, societies or populations; or in de-standardised political paces; and to different informational stereophonic sounds depending on what the right and left hear, and the ability to listen to facts, if at all. Atwood’s aptitude for imagining the unthinkable is noteworthy. So is her ability to understand how social nature, in its individual and collective expressions, can adapt, conform and (yes, ‘and’, not ‘or’) resist a dystopian context. This kind of imagination and sensibility should be, perhaps more than ever before, a public ambition of sociology. Her marked inventiveness and keen perceptiveness are surely attractive to those interested in identifying the long-run longitudinal sequence and coherence of life events. One of the reasons is that this pandemic and its effects disrupt events, their meaningful interrelation and their understanding. The pandemic has consequences at sociological and analytical levels. As such, it is undebatable that the pandemic pokes the 'sociological bear' in each individual (i.e. brings out the sociological critical approach in each of us), and that it retunes the sociologist’s mindset, concerns, commitment and imagination. What is, however, much more debatable is when, how and what to do with this sociological inquietude.